Magnetic Targeted Delivery of Induced Pluripotent Stem Cells Promotes Articular Cartilage Repair. (26th December 2017) - Kotaka, Shinji; Wakitani, Shigeyuki; Shimamoto, Akira; Kamei, Naosuke; Sawa, Mikiya; Adachi, Nobuo; Ochi, Mituo
Abstract : Cartilage regeneration treatments using stem cells are associated with problems due to the cell source and the difficulty of delivering the cells to the cartilage defect. We consider labeled induced pluripotent stem (iPS) cells to be an ideal source of cells for tissue regeneration, and if iPS cells could be delivered only into cartilage defects, it would be possible to repair articular cartilage. Consequently, we investigated the effect of magnetically labeled iPS (m-iPS) cells delivered into an osteochondral defect by magnetic field on the repair of articular cartilage. iPS cells were labeled magnetically and assessed for maintenance of pluripotency by their ability to form embryoid bodies in vitro and to form teratomas when injected subcutaneously into nude rats. These cells were delivered specifically into cartilage defects in nude rats using a magnetic field. The samples were graded according to the histologic grading score for cartilage regeneration . m-iPS cells differentiated into three embryonic germ layers and formed teratomas in the subcutaneous tissue. The histologic grading score was significantly better in the treatment group compared to the control group. m-iPS cells maintained pluripotency, and the magnetic delivery system proved useful and safe for cartilage repair using iPS cells.